Verification of business process workflows - Pranevičius, Henrikas; Misevičienė, Regina (Technological and Economic Development of Economy, 2012)
Modeling of Business processes is essential in many areas. Workflows represent the Business processes. It is possible to identify potential problems while performing verification of workflows. One of the objectives of the verification is to assure reachability. This includes analysis of the deadlock and tempo blocking freeness properties. The paper presents verification approach based on using an adjacency matrix. Spreadsheets are used as a verification tool. The approach is illustrated by the examples which justify the importance of verification in workflow processes.